Overexpression, clinical significance and potential mechanisms of protein kinase D1 in hepatocellular carcinoma: multi-omic analyses and pharmacological insights - Zhen-dong Chen; Hui-ping Lu; Yan-ting Zhan; Fei-yan He; Liang-qin Zhu; Yu-long Deng; Xi-ni Wei; Min-ying Yang; Kai Qin; Yu-xing Tang; Ke-jun Wu; Zhi-guang Huang; et al. (Functional & Integrative Genomics, 2026)

A natural Nlscarlet insertion underlies the orange-eye phenotype and facilitates efficient multiple-sgRNA genome editing in Nilaparvata lugens - Wen-Nan Ye; Rong-Yu Chen; Qi Xing; Yan-Chao Zhang; Shun-Fan Wu; Cong-Fen Gao (Insect Biochemistry and Molecular Biology, 2026)

Arginine-rich hemp seed globulin-tannic acid non-covalent complexation: Structural compaction, enhanced antioxidant/emulsifying properties, and modulated digestibility - Yu Zhang; Xiao-Dong Tian; Zuo-Xing Di; Hai-Bo Jin; Guang-Xiang He; Suo-He Yang; Rong-Yue Zhang; Lei Ma; Xiao-Yan Guo; Peng-Wei Xu (Food Chemistry, 2026)

Field resistance monitoring and nAChR α6 target validation support spinetoram as a candidate insecticide for rotation in Nilaparvata lugens resistance management - Wen-Nan Ye; Qi Xing; Rong-Yu Chen; Yan-Chao Zhang; Shun-Fan Wu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Three new diterpenoids from the aerial parts of Callicarpa macrophylla - Liang Gou; Rong-Shuai Li; Jian-Lin Lai; Yan-Mei Ning; Xue-Ting Ji; Xiong Qiu; Chao Peng; Xiao-Li Li; Xing-Jie Zhang; Wei-Lie Xiao (Natural Product Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Glutamine-hydrolyzing GMP Synthase Gene (guaA) Regulates Siderophore Synthesis in the Nitrogen-fixing Bacterium (NFB) Kosakonia radicincitans GXGL-4A - Er-Xing Wang; Bao-Yun Feng; Ya-Ting Zhang; Meng-Ting Zhang; Lu-Rong Xu; Yan-Wen Xue; Yun-Peng Chen (Current Microbiology, 2026)

Microwave-enhanced carbothermal reduction for efficient recovery of valuable metals from spent lithium-ion batteries - Gui-Rong Zhang; Da-Shuai Li; Xing-Yu Huang; Yuan-Long Liu; Yan-Qing Cheng; Ling Tong (Waste Management, 2026)

Taxonomy and phylogeny of Erysiphe species on Liquidambar formosana (Hamamelidaceae) - Jing Feng; Shuang-Bao Wang; Shu-Yan Liu; Michael Bradshaw; Uwe Braun; Shou-Rong Yu; Guan-Xiu Guan; Dan-Ni Jin; Zhao-Yang Zhang; Han-Xing Gao (New Zealand Journal of Botany, 2025)

Labdane-type diterpenoids from Hypoestes phyllostachya inhibit pancreatic cancer stem cells - Tong Yan; Lin-Fen Ding; Ya Chen; Guo-Xian Hu; Lu Qu; Ming Hu; Ya-Xuan Ma; Rong-Qing Yuan; Lin Jia; Mei-Ju Zhao; Liu-Dong Song; Jia Su; et al. (Phytochemistry, 2025)

The crucial role of immune factors in susceptibility to SARS-CoV-2 infection and severity of COVID-19 - Xing-Hao Yu; Rong-Rong Cao; Yi-Qun Yang; Han-Wen Cao; Fei-Yan Deng; Shu-Feng Lei (Molecular Genetics and Genomics, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Oxygen vacancies-mediated the peracetic acid activation to selectively generate 1O2 for water decontamination - Yi Chen; Qian Li; Ruidian Su; Yixuan Gao; Ning An; Yu Rong; Xing Xu; Defang Ma; Yan Wang; Baoyu Gao (Water Research, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Scalable deposition of SnO2 ETL via SALD for large-area inverted perovskite solar modules - Xuewei Jiang; Bin Shan; Geng Ma; Yan Xu; Xing Yang; Wenbin Zhou; Chenhui Li; Fan Yang; Rong Chen (Chemical Engineering Journal, 2025)

Transcriptome Sequencing Reveals Effects of Artificial Feed Domestication on Intestinal Performance and Gene Expression of Carnivorous Mandarin Fish (Siniperca chuatsi) and Related Mechanisms - Jia-Xing Luo; Xiao-Tian Gao; Zhen Rong; Li-Han Zhang; Yan-Feng Sun; Zun-Li Qi; Qi Yu; Khor Waiho; Wei-Xu Zhao; Yi-Huan Xu; Chun-Long Zhao; Cheng-Bin Wu (Marine Biotechnology, 2025)

Combination of herbal extracts regulates growth performance, liver and intestinal morphology, antioxidant capacity, and intestinal microbiota in Acrossocheilus fasciatus - Yi Ting Shen; Zhi Li Ding; Xiao Yan Wang; Wen Qi Chen; Rong Xing Xia; Shun Yang; Hui Fei (Aquaculture, 2025)

Comparison of the short- and long-term effects of zinc ions on the anaerobic mesophilic co-digestion of food waste and waste activated sludge: Digester performance, antibiotic resistance gene reduction and the microbial community - Bao-Shan Xing; Yi-Meng Su; Yu-Lin Fu; Yi-Fan Wu; Chen-Hao Yan; Xiaochang C. Wang; Yu-You Li; Rong Chen (Journal of Hazardous Materials, 2024)

Immunoprotective effect of recombinant Lactobacillus plantarum expressing largemouth bass virus MCP on largemouth bass - Yong-Lei Yang; Rong-Rong Zhang; Jing-Yi Pang; Jun-Hong Xing; Tian-Kui Guo; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; Jian-Zhong Wang; Xin Cao; Nan Wang; et al. (Fish & Shellfish Immunology, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Argon non-thermal plasma treatment promotes the development of rice (Oryza sativa L.) in saline alkali environments - Kai Liu; Yan-Jiang Feng; Jun-Xiang Guo; Gui-Ling Wang; Li-Li Shan; Shi-Wei Gao; Qing Liu; Hu-Nan Sun; Xi-Yu Li; Xing-Rong Sun; Jing-Yang Bian; Taeho Kwon (Protoplasma, 2024)

Lensless shadow microscopy-based shortcut analysis strategy for fast quantification of microplastic fibers released to water - Yu Su; Chenqi Yang; Yao Peng; Cheng Yang; Yanhua Wang; Yong Wang; Feng Yan; Baoshan Xing; Rong Ji (Water Research, 2024)

Small water body significantly contributes to nitrous oxide emissions in China's aquaculture - Xing Yan; Haojie Han; Xiaohan Li; Xiangmin Rong; Longlong Xia; Xiaoyuan Yan; Yongqiu Xia (Journal of Environmental Management, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

A Pennsylvanian rugose coral assemblage from eastern Junggar Basin, Northwest China - Sun-Rong Yang; Le Yao; Zhang-Shuai Hou; Xun-Yan Ye; Ying Li; Xing Huang; Shu-Zhong Shen; Xiang-Dong Wang (Palaeoworld, 2024)

ZnO nanorod coatings attenuate antibiotic resistance genes (ARGs) on their surface biofilms in estuarine environment - Xing-pan Guo; Rong-rong Sha; Yu-cen Wang; Jia Yan; Bo Peng; Zuo-shun Niu; Wen-liang Liu; Xin Li; Yi Yang (Journal of Environmental Chemical Engineering, 2024)

Modulation of plasmacytoid dendritic cell and CD4+ T cell differentiation accompanied by upregulation of the cholinergic anti-inflammatory pathway induced by enterovirus 71 - Li Li; Rong-Wei Huang; Xiao-Ning Liu; Xiao-Yi Xiang; Yuan-Tao Zhou; Xing-Xing Feng; Lv-Yuan Tao; Jia Yu; Qin Yi; Yan-Chun Wang; Xiao-Mei Liu (Archives of Virology, 2024)

Dissolved organic carbon and dissolved oxygen determine the nitrogen removal rate constant in small water bodies of intensive agricultural region - Xing Yan; Haojie Han; Xiaohan Li; Jiong Wen; Xiangmin Rong; Yongqiu Xia; Xiaoyuan Yan (Agriculture, Ecosystems & Environment, 2024)

A pleiotropic SIS-based hydrogel with immunomodulation via NLRP3 inflammasome inhibition for diabetic bone regeneration - Ning Sheng; Fei Xing; Qing-Yi Zhang; Jie Tan; Rong Nie; Kai Huang; He-Xi Li; Yan-Lin Jiang; Bo Tan; Zhou Xiang; Hui-Qi Xie (Chemical Engineering Journal, 2024)

Lack of the CCT domain changes the ability of mango MiCOL14A to resist salt and drought stress in Arabidopsis - Shu-Quan Chen; Cong Luo; Yuan Liu; Rong-Zhen Liang; Xing Huang; Ting-Ting Lu; Yi-Hang Guo; Ruo-Yan Li; Chu-Ting Huang; Zhuo Wang; Xin-Hua He (Plant Science, 2023)

The early Late Triassic Yumen mafic rocks in the eastern Tethyan Himalaya: A record of the progressive opening of the Yarlung Zangbo Neo-Tethyan Ocean - Wei-Liang Liu; Zhong-Xi Xia; Yun Zhong; Chris Yakymchuk; Zhou-Rong Cai; He Xiao; Xing Liao; Chi Yan; Ru-Xin Ding; Jin-Nan Liu (Lithos, 2023)

Multiomics reveals new biomarkers and mechanistic insights into the combined toxicity effects of 2,2′,4,4′,5,5′-hexachlorobiphenyl and atrazine exposures in MCF-7 cells - Yu-Shun Lu; Xing Wen; Ju Chen; Xiao-Rong He; Jiang Yu; Jing Qiu; Yong-Zhong Qian; Yan-Yang Xu (Environmental Pollution, 2023)

A systematic analysis and evaluation of nutritional composition of 23 strains of marine microalgae commonly used in aquaculture - Jia-Xing Zhang; Zhao-Shou Ran; Hai-Xuan Xie; Fei Kong; Meng-Qi Zhang; Yao Zhou; Yan-Rong Li; Kai Liao; Xiao-Jun Yan; Ji-Lin Xu (Algal Research, 2023)

Advances in post-operative prognostic models for hepatocellular carcinoma - Ziqin He; Xiaomin She; Ziyu Liu; Xing Gao; Lu Lu; Julu Huang; Cheng Lu; Yan Lin; Rong Liang; Jiazhou Ye (Journal of Zhejiang University-SCIENCE B, 2023)

Remodeled CD146+CD271+ Bone Marrow Mesenchymal Stem Cells from Patients with Polycythemia Vera Exhibit Altered Hematopoietic Supportive Activity - Chao Chen; Mingying Zhang; Rong Li; Jiajia Yuan; Jinqiang Yan; Yuhui Zhang; Wen Xing; Jie Bai; Yuan Zhou (Stem Cell Reviews and Reports, 2023)

Exposure–response relationship between temperature, relative humidity, and varicella: a multicity study in South China - Yihan Li; Jialing Li; Zhihua Zhu; Weilin Zeng; Qi Zhu; Zuhua Rong; Jianxiong Hu; Xing Li; Guanhao He; Jianguo Zhao; Lihua Yin; Yi Quan; et al. (Environmental Science and Pollution Research, 2023)

Wisdom, predicaments, and challenges of a millennium ancient weir—Dujiangyan Project - Xiao-rong Huang; Xing-yu Zhou; Jin-jun You; Qing Yang; Yan-jun Wang; Kai Ma (Journal of Mountain Science, 2021)

A stable QTL qSalt-A04-1 contributes to salt tolerance in the cotton seed germination stage - Qishen Gu; Huifeng Ke; Chenchen Liu; Xing Lv; Zhengwen Sun; Zhengwen Liu; Wei Rong; Jun Yang; Yan Zhang; Liqiang Wu; Guiyin Zhang; Xingfen Wang; et al. (Theoretical and Applied Genetics, 2021)

Clinical study on empirical and diagnostic-driven (pre-emptive) therapy of voriconazole in severe aplastic anaemia patients with invasive fungal disease after intensive immunosuppressive therapy - Yuhong Wu; Li Yan; Huaquan Wang; Hong Liu; Limin Xing; Rong Fu; Zonghong Shao (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Construction and characterization of UAA-controlled recombinant Zika virus by genetic code expansion - Rong-Rong Zhang; Qing Ye; Xiao-Feng Li; Yong-Qiang Deng; Yan-Peng Xu; Xing-Yao Huang; Qing Xia; Cheng-Feng Qin (Science China Life Sciences, 2021)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Grape seed proanthocyanidin extract ameliorates hepatic lipid accumulation and inflammation in grass carp (Ctenopharyngodon idella) - Rong-Hua Lu; Chao-Bin Qin; Feng Yang; Wen-Ya Zhang; Yu-Ru Zhang; Guo-Kun Yang; Li-Ping Yang; Xiao-Lin Meng; Xiao Yan; Guo-Xing Nie (Fish Physiology and Biochemistry, 2020)

Roles of PTBP1 in alternative splicing, glycolysis, and oncogensis - Wei Zhu; Bo-lun Zhou; Li-juan Rong; Li Ye; Hong-juan Xu; Yao Zhou; Xue-jun Yan; Wei-dong Liu; Bin Zhu; Lei Wang; Xing-jun Jiang; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Regulation of growth performance and lipid metabolism in juvenile grass carp (Ctenopharyngodon idella) with honeysuckle (Lonicera japonica) extract - Xiao-Lin Meng; Zhen-Xiang Zhu; Rong-Hua Lu; Shuai Li; Wen-Pan Hu; Chao-Bin Qin; Xiao Yan; Guo-kun Yang; Guo-Xing Nie (Fish Physiology and Biochemistry, 2019)

An integrated prevention strategy to address problems associated with continuous cropping of watermelon caused by Fusarium oxysporum - Fu-Yan Liu; Qiang Zhu; Hu-Rong Yang; Jun Zhou; Chuan-Chao Dai; Xing-Xiang Wang (European Journal of Plant Pathology, 2019)

Skin test of tuberculin purified protein derivatives with a dissolving microneedle-array patch - Wei Wang; Hou Ming Liu; Jing Zhou; Yu Guang Wang; Xi Feng; Hao Tang; Qinying Yan; Rong Sheng Zhu; Yu Wei Wu; Xing Guo Wang; Dan He; Fan Chen (Drug Delivery and Translational Research, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

Two new Anti-TMV active chalconoid analogues from the root of Phyllanthus emblica - He Yan; Li Rong Han; Xing Zhang; Jun Tao Feng (Natural Product Research, 2017)

Nocardia tengchongensis sp. nov., isolated from a soil sample - Shuai Li; Hong Ming; Yan-Yan Duan; Jian-Rong Huang; Zhuo-Li Zhao; Ling-Yu Zhang; Wei-Li Ji; Xiao-Lin Meng; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2017)

A Volumetric and Functional Connectivity MRI Study of Brain Arginine-Vasopressin Pathways in Autistic Children - Xiao-Jing Shou; Xin-Jie Xu; Xiang-Zhu Zeng; Ying Liu; Hui-Shu Yuan; Yan Xing; Mei-Xiang Jia; Qing-Yun Wei; Song-Ping Han; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Nanomaterials for water pollution monitoring and remediation - Xing-yan Xue; Rong Cheng; Lei Shi; Zhong Ma; Xiang Zheng (Environmental Chemistry Letters, 2017)

Tenuigenin promotes the osteogenic differentiation of bone mesenchymal stem cells in vitro and in vivo - Hua-ji Jiang; Xing-gui Tian; Shou-bin Huang; Guo-rong Chen; Min-jun Huang; Yu-hui Chen; Bin Yan; Sheng-fa Li; Jia-jun Tang; Hui-yu Zhao; Liang Wang; Zhong-min Zhang (Cell and Tissue Research, 2017)

Co-expression of MtDREB1C and RcXET Enhances Stress Tolerance of Transgenic China Rose (Rosa chinensis Jacq.) - Ji-Ren Chen; Yan-Bin Chen; Monika Ziemiańska; Rong Liu; Zi-Niu Deng; Irena Niedźwiecka-Filipiak; Yan-Lin Li; Jin-Xia Jiao; Xing-Yao Xiong (Journal of Plant Growth Regulation, 2016)

Sinomonas halotolerans sp. nov., an actinobacterium isolated from a soil sample - Qian-Qian Guo; Hong Ming; Xiao-Lin Meng; Jian-Rong Huang; Yan-Yan Duan; Shan-Hui Li; Shuai Li; Jian-Xin Zhang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2015)

New cytotoxic and anti-inflammatory compounds isolated from Morus alba L. - Jing Qin; Min Fan; Juan He; Xing-De Wu; Li-Yan Peng; Jia Su; Xiao Cheng; Yan Li; Ling-Mei Kong; Rong-Tao Li; Qin-Shi Zhao (Natural Product Research, 2015)

Rhodococcus agglutinans sp. nov., an actinobacterium isolated from a soil sample - Qian-Qian Guo; Hong Ming; Xiao-Ling Meng; Yan-Yan Duan; Rui Gao; Jian-Xin Zhang; Jian-Rong Huang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2015)

Effects of Recombinant Human AMH on SCF Expression in Human Granulosa Cells - Rong Hu; Yan Lou; Fei-Miao Wang; Hui-Ming Ma; Xing Wu; Xiao-Mei Zhang; Juan Li; Ying-Pu Sun (Cell Biochemistry and Biophysics, 2013)

Genetic diversity analysis of Rhododendron aureum Georgi (Ericaceae) located on Changbai Mountain using ISSR and RAPD markers - Yan-Fei Liu; Ming Xing; Wei Zhao; Rong-Jun Fan; Su Luo; Xia Chen (Plant Systematics and Evolution, 2012)

Malignant transformation of 293 cells induced by ectopic expression of human Nanog - Yan-Li Lin; Zheng-Bin Han; Fu-Yin Xiong; Li-Yuan Tian; Xiao-Jie Wu; Shi-Wei Xue; Yan-Rong Zhou; Ji-Xian Deng; Hong-Xing Chen (Molecular and Cellular Biochemistry, 2011)

Effects of elevated CO2 levels on root morphological traits and Cd uptakes of two Lolium species under Cd stress - Yan Jia; Shi-rong Tang; Xue-hai Ju; Li-na Shu; Shu-xing Tu; Ren-wei Feng; Lorenzino Giusti (Journal of Zhejiang University-SCIENCE B, 2011)

Chemometrics-based approach to modeling quantitative composition-activity relationships for Radix Tinosporae - Shi-Kai Yan; Zhong-Ying Lin; Wei-Xing Dai; Qi-Rong Shi; Xiao-Hua Liu; Hui-Zi Jin; Wei-Dong Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2010)

An investigation of hormesis of trichloroethylene in L-02 liver cells by differential proteomic analysis - Hai-Yan Huang; Jian-Jun Liu; Ren-Rong Xi; Xiu-Mei Xing; Jian-Hui Yuan; Lin-Qing Yang; Gong-Hua Tao; Chun-Mei Gong; Zhi-Xiong Zhuang (Molecular Biology Reports, 2009)

Isolation and Evolution Mode Analysis of NBS–LRR Resistance Gene Analogs from Hexaploid Wheat - De-Shun Feng; Yan Li; Hong-Gang Wang; Xing-Feng Li; Ju-Rong Gao (Plant Molecular Biology Reporter, 2009)

Lance-adams syndrome: a report of two cases - Yan-xing Zhang; Jian-ren Liu; Biao Jiang; Hui-qin Liu; Mei-ping Ding; Shui-jiang Song; Bao-rong Zhang; Hong Zhang; Bin Xu; Huai-hong Chen; Zhong-jin Wang; Jian-zheng Huang (Journal of Zhejiang University-SCIENCE B, 2007)